Improved detection of molecularly targeted iron oxide particles in mouse brain using B0 field stabilised high resolution MRI - Gilchrist, S; Kinchesh, P; Zarghami, N; Khrapitchev, AA; Sibson, NR; Kersemans, V; Smart, SC (Elsevier, 2020)
Purpose: High resolution multi-gradient echo (MGE) scanning is typically used for detection of molecularly targeted iron oxide particles. The images of individual echoes are often combined to generate a composite image with improved SNR from the early echoes and boosted contrast from later echoes. In 3D implementations prolonged scanning at high gradient duty cycles induces a B0 shift that predominantly affects image alignment in the slow phase encoding dimension of 3D MGE images. The effect corrupts the composite echo image and limits the image resolution that is realised. A real-time adaptive B0 stabilisation during respiration gated 3D MGE scanning is shown to reduce image misalignment and improve detection of molecularly targeted iron oxide particles in composite images of the mouse brain.